Finansowanie zobowiązań akcesyjnych Polski w zakresie ochrony środowiska - Burzyńska, Dorota (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Environmental and social purposes are supported by EU funds with appropriate committal public and private means. Polish accession to European Union opened up opportunities to exercise of Commonwealth means. Simultaneously the realization of accepted access obligations requires describing expenditure of money on ecological investments. Entities are very interested in realization of ecological ventures. It manifests in realization of many executive programmes. Many attempts have been made to estimate costs of initiating directives and expenditures on separated spheres of activities for example: residuary, industrial waste or water economy. This article is an attempt to put in order and to show scale of means that are assigned for protective tasks from EU and domestic means. The open question for accomplishing investments is assignation actual sources their financing. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 93-102